2020
DOI: 10.21203/rs.3.rs-114837/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Soluble Urokinase-Type Plasminogen Activator Receptor (suPAR) is a Risk Indicator for eGFR Loss in Kidney Transplant Recipients

Abstract: Background suPAR is a signaling protein of the Ly6/alpha-neurotoxin family. In the kidney, suPAR contributes to podocyte foot process effacement and glomerular barrier function disruption via activating αvβ3 integrin on the podocyte membrane. Its role in allograft function or transplant-specific outcomes needs clarification. Therefore, we prospectively investigated the prognostic relevance of suPAR in patients before and one year after kidney transplantation (KTx).Methods We included 100 patients who had recei… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
0
0
Order By: Relevance
“…In a broad, unselected hemodialysis cohort, a high suPAR level was a predictor of all-cause mortality (hazard ratio [HR] = 1.91, 95% CI = 1.47-2.48, p < 0.001), CV mortality (HR = 1.47, 95% CI = 1.03-2.09, p = 0.03), and non-CV mortality (HR = 1.94, 95% CI = 1.28-2.93, p = 0.002) [10]. A subsequent prospective study of 100 KT recipients demonstrated a significant decrease in suPAR levels posttransplant [11], with a strong correlation observed between suPAR levels at 1-year post-KT and eGFR loss, highlighting its potential for early detection of allograft dysfunction. However, in our study, the suPAR level negatively correlated with eGFR but lacked statistical significance.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In a broad, unselected hemodialysis cohort, a high suPAR level was a predictor of all-cause mortality (hazard ratio [HR] = 1.91, 95% CI = 1.47-2.48, p < 0.001), CV mortality (HR = 1.47, 95% CI = 1.03-2.09, p = 0.03), and non-CV mortality (HR = 1.94, 95% CI = 1.28-2.93, p = 0.002) [10]. A subsequent prospective study of 100 KT recipients demonstrated a significant decrease in suPAR levels posttransplant [11], with a strong correlation observed between suPAR levels at 1-year post-KT and eGFR loss, highlighting its potential for early detection of allograft dysfunction. However, in our study, the suPAR level negatively correlated with eGFR but lacked statistical significance.…”
Section: Discussionmentioning
confidence: 95%
“…The soluble urokinase plasminogen activator receptor (suPAR), a key player in inflammation and fibrinolysis, has emerged as a predictive marker for CVD and atherosclerosis development [7][8][9]. Previous studies have established a link between suPAR levels and chronic kidney disease (CKD), with high suPAR levels robustly predicting allcause and cardiovascular mortality in a large hemodialysis population in Italy [10,11]. In a prospective study of KT recipients, suPAR levels significantly dropped after resolving the end-stage renal disease status.…”
Section: Introductionmentioning
confidence: 99%